2021
DOI: 10.1177/13684302211030009
|View full text |Cite
|
Sign up to set email alerts
|

When White Americans see “non-Whites” as a group: Belief in minority collusion and support for White identity politics

Abstract: White Americans may find diversity threatening in part because they construe non-White Americans as a coherent social and political force. We argue that this perception manifests in a belief that minority groups collude against White people and that White people should act as a political bloc to defend ingroup interests. In a 3-year longitudinal study, the belief in minority collusion and support for White identity politics increased significantly among a nationally representative sample of 2,635 White America… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 76 publications
(129 reference statements)
3
24
1
Order By: Relevance
“…Despite finding that variables such as SDO, group threat, and the endorsement of legitimizing myths each predicted greater perceived discrimination against their own dominant group (i.e., White Americans or men), there was little (or mixed) evidence regarding SDO x Threat interactions. In contrast to some of the other papers in the Special Issue (e.g., Domen, Scheepers, Derks and van Veelen 2022; Earle & Hodson, 2022;Knowles, Tropp and Mogami 2022;Stefaniak & Wohl, 2022), but in keeping with others (e.g., Stewart & Willer, 2022), threat effects in this project were not moderated by individual differences.…”
Section: Gender Shiftscontrasting
confidence: 73%
See 1 more Smart Citation
“…Despite finding that variables such as SDO, group threat, and the endorsement of legitimizing myths each predicted greater perceived discrimination against their own dominant group (i.e., White Americans or men), there was little (or mixed) evidence regarding SDO x Threat interactions. In contrast to some of the other papers in the Special Issue (e.g., Domen, Scheepers, Derks and van Veelen 2022; Earle & Hodson, 2022;Knowles, Tropp and Mogami 2022;Stefaniak & Wohl, 2022), but in keeping with others (e.g., Stewart & Willer, 2022), threat effects in this project were not moderated by individual differences.…”
Section: Gender Shiftscontrasting
confidence: 73%
“…These constructs, in many ways, capture the notion of a loss of privilege, with an eye to what dominant groups once had as opposed to simply what they stand to lose. In their work, Knowles, Tropp and Mogami (2022) used longitudinal data to explore latent growth curve trends that can also shed light on how processes unfold (over time): Whites' essentialist beliefs of their ingroup predicted beliefs in minority collusion downstream; beliefs in minority collusion lowered support for BLM and elevated support for the Alt-Right downstream.…”
Section: Processes Underlying Shift Reactionsmentioning
confidence: 99%
“…Research on White Americans suggests a perception of coalitions as creating strength in numbers. For example, many White Americans fear the growing percentage of people of color in the US (Craig & Richeson, 2014a; Craig et al, 2018) and are threatened by coalitions of stigmatized social groups (Knowles et al, in press). The present research demonstrated for the first time that heterosexual White men may endorse stigma-based solidarity, and that this endorsement is greater when prejudices are believed to co-occur, but that this did not translate to support for coalitions.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, to our knowledge, past research has not explored the effects of cisgender heterosexual White men’s endorsement of stigma-based solidarity on support for social justice efforts. While recent research has suggested that White Americans may be threatened by intraminority coalitions (Knowles et al, in press), it is unclear the extent to which they believe stigmatized social groups should work together to achieve equality, and if that belief translates to their own efforts for equality. Nevertheless, past research has found that White men do perceive prejudices as co-occurring (e.g., Sanchez et al, 2017), and we hypothesized that the manipulations would again significantly shift self-reported LTGP.…”
Section: Studymentioning
confidence: 99%
“…1 Although much media attention has focused on the observed decline of non-Hispanic Whites, there has been an even more remarkable increase in the proportion of people of color (PoC), with African Americans, Asian Americans, and Latinos now representing 37% of the United States population (Bahrampour and Mellnik 2021). Many White individuals believe this increase in PoC augurs greater political power for minoritized groups at the expense of Whites (Knowles, Tropp, and Mogami 2021;Jardina 2019). Yet prior work suggests that political unity among people of color is difficult to harness toward civic ends because Blacks, Asians, and Latinos hail from distinct groups who arrived to the U.S. under different conditions; are treated in assorted ways by U.S. society; and, have varied political priorities (e.g., Carter 2019;Benjamin 2017;Wilkinson 2015;Mora 2014;Masuoka and Junn 2013;Kim 2003;Tuan 1998).…”
mentioning
confidence: 99%